The Influence of Transformational Leadership, Organizational Climate, Innovative Behavior and Employee Engagement on Industrial Employee Performance With Job Satisfaction in the Digital Era - Prayuda, Rafie (Journal of Industrial Engineering & Management Research, 2019)
The purpose of this research is to analyze and test the Effect of Transformational Leadership, Organizational Climate, Innovative Behavior on Performance with Job Satisfaction as the intervening variable. This research design uses a quantitative survey method with data collection through online questionnaires to 166 industrial employee respondents in Tangerang. Data analysis uses structural equation modeling (SEM) with data processing tools SmartPLS 3.0 program. The results of this study indicate that: (1) Transformational Leadership, Organizational Climate, and Innovative Behavior have a positive and significant effect on job satisfaction. (2) Transformational Leadership, Organizational Climate, Employee Engagement have a positive and significant effect on performance. (3) Employee Engagement has a positive and insignificant effect on job satisfaction (4) Innovative behavior has a positive and insignificant effect on employee performance. (5) Transformational Leadership, Organizational Climate, Innovative Behavior, Employee Engagement have a positive and significant effect on Employee Performance through Job Satisfaction.